MULES, FUELS, AND FUSION: ENERGY, ENTROPY, AND THE CROSSING OF THE PANAMANIAN TRANSIT ZONE, 1848-1990 - Coulombe, Jordan T (University of New Hampshire Scholars' Repository, 2019)
Between 1848 and 1990 Americans attempted to construct numerous infrastructural projects in Panama in hopes of bridging the Isthmus and connecting the seas. These schemes ran the gamut from the creation of the Panama railroad in the early 1850s through attempts to detonate nuclear explosives to create a sea-level canal in the 1960s. While these projects seem quite alien to one another, these two plans, and other attempts to cross the Isthmus, were unified by their shared reliance on energy’s capacity to overcome the entropy of the Panamanian environment. In order to reshape Isthmian landscapes, American engineers, scientists, and policymakers had to first harness and unleash a variety of energy sources that could do the work of moving earth, constructing structures, and imposing order on the Panamanian landscape. Their efficacy was always mediated by entropy, the environment’s tendency to trend towards disorder. Without constant injections of energy, the fluid Panamanian landscape would shift and move, destabilizing the landscape and wrecking human altered landscapes. This contentious relationship between energy and entropy catalyzed an energetic arms race in which Americans looked towards increasingly powerful sources of energy to hold entropy at bay. Ultimately this proved a double-edged sword. By altering the environment in increasingly complex ways, they simultaneously created the potential for increasing volumes of entropy. This positive feedback loop forced humans to consume more energy to contain entropy, thus restarting the cycle of energetic and entropic growth. This project tracks this process starting with the creation of the railroad and follows it through the creation of the Panama Canal in the first two decades of the 1900s, initial attempts to restructure the Canal during the interwar years, the attempt to build a new canal through the use of nuclear excavation, and finally attempts to use the Isthmus to facilitate the transportation of Alaska North Slope oil during the 1970s and 1980s. Along the ...